2021
DOI: 10.1111/papt.12331
|View full text |Cite
|
Sign up to set email alerts
|

A treatment protocol to guide the delivery of dialogical engagement with auditory hallucinations: Experience from the Talking With Voices pilot trial

Abstract: Purpose To present a treatment protocol for delivering Talking With Voices, a novel intervention for people with psychosis that involves dialogical engagement with auditory hallucinations. Method This paper presents a manualized approach to therapy employed in the Talking With Voices trial, a feasibility and acceptability randomized control trial of 50 adult participants. A rationale for following a treatment manual is provided, followed by the theoretical underpinnings of the intervention and its principles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
2
12
0
2
Order By: Relevance
“…Much like other clinical groups who describe voice‐like experiences (e.g., individuals diagnosed with psychosis; Longden, Corstens, Morrison, et al, 2021; Schnackenberg, Fleming, Walker, & Martin, 2018), satisfaction with Voice Dialogue was generally high amongst individuals in this study. Participants felt that the dialogical process provided insights into the functions, intentions, consequences, and vulnerabilities underlying their EDV.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Much like other clinical groups who describe voice‐like experiences (e.g., individuals diagnosed with psychosis; Longden, Corstens, Morrison, et al, 2021; Schnackenberg, Fleming, Walker, & Martin, 2018), satisfaction with Voice Dialogue was generally high amongst individuals in this study. Participants felt that the dialogical process provided insights into the functions, intentions, consequences, and vulnerabilities underlying their EDV.…”
Section: Discussionsupporting
confidence: 65%
“…Accordingly, the aim of talking with voices is to comprehend the biography, meaning, and intentions of voices and resolve voice‐hearer conflicts (Corstens et al, 2012). Studies suggest that, for people experiencing psychosis, Voice Dialogue provides understanding and increased control over voices and reduces voice‐related distress (Longden, Corstens, Morrison, et al, 2021; Longden, Corstens, Pyle, et al, 2021; Schnackenberg, Fleming, Walker, & Martin, 2018; Steel et al, 2020). However, research is yet to explore the applications of Voice Dialogue to voices experienced in other groups.…”
Section: Introductionmentioning
confidence: 99%
“…Therapy for individuals diagnosed with psychosis who experience auditory hallucinations can similarly use dialogical methods that attempt to correct fear or passivity when hearing voices and create a more constructive relationship with them. The aim is to understand the role of the voices and relate to them as useful rather than problematic parts of the self that are the products of the individual’s life history (Longden et al, 2021). The creation of a comprehensive mental model of the self is part of mentalization treatment for BPD, which recognizes that an inability to mentalize leads to major problems in affect regulation (Bateman & Fonagy, 2010).…”
Section: Implications For the Assessment And Treatment Of Icd-11 Cptsdmentioning
confidence: 99%
“…Similarly, relationally based therapies, such as relating therapy (Hayward et al, 2017; Paulik et al, 2013), the Talking With Voices approach (e.g. Longden et al, 2021), or AVATAR therapy (Craig et al, 2018; Ward et al, 2020) may be indicated where relationships with voices mirror past experiences of discrimination, victimization, or marginalization and this appears to fuel negative content. Large trials that assess negative voice content as an outcome and which use mediation analysis to assess mechanisms of change in therapy would provide increased knowledge in this area.…”
Section: Discussionmentioning
confidence: 99%